Studi Kinetika Reaksi Metanolisis Pembuatan Metil Ester Sulfonat (MES) Menggunakan Reaktor Batch Berpengaduk - Abdul Chalim; Agung Ari Wibowo; Ade Sonya Suryandari; Muhammad Muhajjir Syarifuddin; Moh. Tohir (Politeknik Negeri Malang, 2017)
Surfactant is a surface active agent which is widely applied in chemical industry related to its ability to stabilize the emulsion between the oil phase and the water phase. Surfactant-based on vegetable oil is a technology developed in the field of surfactant which has been dominated by surfactants made from petroleum. Methyl ester sulfonate (MES) is an anionic surfactant produced by the reaction between fatty acid methyl ester with a sulfonating agent or called as sulfonation reaction. MES undergoes an advanced process called methanolysis and neutralization reactions. This study investigated the effect of reactant molar ratio, reaction time and reaction temperature on MES yield on methanolysis reaction. The highest MES yield of 49.71% was achieved at a reaction temperature of 120°C, the reaction time of 120 minutes and the molar ratio between MES and methanol of 1:3. The rate constants of methanolysis reactions are determined by reacting the reactants in the stirred batch reactor under those operating conditions.